JUBILEU DE OURO DO CURSO DE ENFERMAGEM UFPR: O QUE ALMEJAMOS PARA OS PRÓXIMOS 50 ANOS? - Figueiredo, Karla Crozeta; Macedo, Laura Christina; Miranda, Fernanda Moura D'Almeida (Cogitare Enfermagem, 2024)
Editorial.